Conducting focus groups in realist evaluation. (October 2022) - Manzano, Ana
Focus groups are valuable tools for evaluators to help stakeholders to clarify programme theories. In 1987, R.K. Merton, often attributed with the birth of focus groups, wrote about how these were 'being mercilessly misused'. In the 1940s, his team had conceived focus groups as tools for developing middle-range theory, but through their astonishing success focus groups have metamorphosed and are often an 'unchallenged' choice in many evaluation approaches, while their practice seems to provide a philosophically diverse picture. This article examines what knowledge focus group data generate, and how they support theory development. It starts with an overview of the history of focus groups, establishing a relationship between their emergence as a data collection method and the evaluation profession. Practical lessons for conducting groups in realist evaluation are suggested, while exploring how qualitative data can support programme and middle-range theory development using the example of realist evaluation.